Inequalities and disparities in health care and health concerns of patients, providers and insurers - Kronenfeld, Jennie J. (Amsterdam ; Boston : Elsevier JAI, 2008)
This volume deals with the topic of health inequalities and health disparities. The volume is divided into five sections. The first section includes an introductory look at the issue of health care inequalities and disparities and also an introduction to the volume. One of the backdrops to this topic in the United States was The National Healthcare Disparities Report and its focus on the ability of Americans to access health care and variation in the quality of care. Disparities related to socioeconomic status were included, as were disparities linked to race and ethnicity and the report also tried to explore the relationship between race/ethnicity and socioeconomic position, as explained in more detail in the first article in the book.The second article discusses a newer overall approach to issues related to health inequalities and health disparities. The remaining four sections of the book address more specific topics relating to inequalities and disparities. The second section examines racial and ethnic inequalities and disparities. The third section includes articles that address the issue from the perspective of research about health care providers and health care facilities. The last two sections of the book focus on consumers and topics of health care disparities, with Section 4 focused on issues related to substance abuse, mental health and related concerns. Section 5 includes articles looking at issues of vulnerable women, women with breast cancer and people with colorectal cancer. "Inequalities and Disparities in Health Care and Health" is important reading for medical sociologists and people working in other social science disciplines studying health-related issues. The volume also provides vital information for health services researchers, policy analysts and public health researchers. The chapters focus on the topics of health inequalities and health disparities. The book is essential for medical sociologists and others in social science industries studying health-related issues.
Includes bibliographical references.
Description based on print version record.
Keywords: Health services accessibility -- United States; Social medicine -- United States; Discrimination in medical care -- United States; Mental health services -- Utilization -- United States; Health systems & services; Medical -- Health Care Delivery; Electronic books